2020
DOI: 10.3390/nu12092627
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Chronic Liver Disease and Portal Hypertension: Potential of DHA as Nutraceutical

Abstract: Chronic liver disease constitutes a growing public health issue worldwide, with no safe and effective enough treatment clinical scenarios. The present review provides an overview of the current knowledge regarding advanced chronic liver disease (ACLD), focusing on the major contributors of its pathophysiology: inflammation, oxidative stress, fibrosis and portal hypertension. We present the benefits of supplementation with docosahexaenoic acid triglycerides (TG-DHA) in other health areas as demonstrated experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 87 publications
(99 reference statements)
2
10
0
2
Order By: Relevance
“…Moreover, in return, the accelerated generation of ROS worsened the oxidative degree to the body. Similar trends of the elevated ROS levels, along with the lipid oxidation, were demonstrated not only in the organs of NAFLD/NASH [46,47], but also of other metabolic syndromes, such as diabetes mellitus [16,48], hypertension [49,50], CKD [51,52], and atherosclerosis [53]. Furthermore, the deficiency of the physiological lipids, particularly PUFA, ethanolamine phospholipids, and CL, leads to biomembrane dysfunction-related disturbances, especially mitochondrial dysfunction, which could oppositely cause free radical production and lipid peroxidation [29,54].…”
Section: Accumulation Of Oxidized Lipid Species In Liver and Kidney Of Nash Model Micesupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, in return, the accelerated generation of ROS worsened the oxidative degree to the body. Similar trends of the elevated ROS levels, along with the lipid oxidation, were demonstrated not only in the organs of NAFLD/NASH [46,47], but also of other metabolic syndromes, such as diabetes mellitus [16,48], hypertension [49,50], CKD [51,52], and atherosclerosis [53]. Furthermore, the deficiency of the physiological lipids, particularly PUFA, ethanolamine phospholipids, and CL, leads to biomembrane dysfunction-related disturbances, especially mitochondrial dysfunction, which could oppositely cause free radical production and lipid peroxidation [29,54].…”
Section: Accumulation Of Oxidized Lipid Species In Liver and Kidney Of Nash Model Micesupporting
confidence: 62%
“…In contrast, there was no such difference for the kidney (Normal, 1462.5 nmol/g; NASH, 1382.2 nmol/g). Taking consideration of the molecular composition, as Figure 2C shows, the total TG accumulation in the NASH liver was predominantly due to the accretion of the more saturated species, especially those with shorter carbon chain length (i.e., [44][45][46][47][48][49][50][51][52][53][54] and fewer double bonds (i.e., 0-4). Even for the longer chain (e.g., C60) TG species, the changing trends depended on double bonds: those with fewer double bonds increased, and those with more double bonds decreased.…”
Section: Tg Accumulation In Nash Liver and Profile Alteration In Nash Kidneymentioning
confidence: 99%
“…A large number of studies have shown that the degree of portal hypertension is an important prognostic factor for liver dysfunction. , Additionally, necrotizing inflammation of the liver can promote the increase of hepatic vascular tension . At the same time, hypertension is also the main cause of chronic kidney disease .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the Mediterranean diet has proven to be beneficial in NAFLD development, mainly due to its high content of polyphenols, vitamins and other molecules with anti-inflammatory and antioxidant effects [242,243]. Specifically, polyphenolic compounds such as resveratrol [244,245] or curcumin [208], or the omega-3 fatty acid, docosahexaenoic acid (DHA) [246], have also shown an improvement in different characteristics of CLD, mainly regarding oxidative stress, inflammation and lipid accumulation, accompanied by the amelioration of HSCs, hepatocytes and KC functions [247,248].…”
Section: Diet and Nutraceuticalsmentioning
confidence: 99%